Comparison of antigens in sonic and pressure cell extracts of Mycobacterium tuberculosis. - Janicki, B W (1976)
Comparisons were made of the yield, chemical content, and biological activity of filtrates and extracts obtained by sonic and pressure cell disruption of bacilli from 4- and 8-week-old Proskauer and Beck cultures of the H37Rv strain (TMC no. 102) of Mycobacterium tuberculosis. The culture filtrates were dialyzed, freeze-dried, reconstituted in saline, and sterilized by membrane filtration. The viable bacilli were washed and resuspended in distilled water and subsequently disrupted either by sonication in the cold for 15 or 30 min or by treatment at 20,000 or 40,000 lb/in2 in a pressure cell. The resulting extracts were clarified by centrifugation, concentrated, and sterilized by filtration. All preparations were adjusted to contain 10 mg of solids (dry weight)/ml and were analyzed quantitatively for protein, deoxyribonucleic acid, ribonucleic acid, polysaccharide, and lipid content. Separation patterns obtained by gradient acrylamide gel electrophoresis, as well as by one- and two-dimensional immunoelectrophoresis, provided the basis for qualitative comparisons of the culture filtrates and cell extracts. Three-point dose-response curves also were used to compare the preparations for skin test reactivity in BCG-vaccinated guinea pigs. It was concluded that, although there were no consistent differences in chemical content or biological activity between the preparations, a 15-min sonic treatment appeared to be the most suitable method for preparation of bacillary extracts based on yield of active components and ease of preparation.